Degradable adhesive tape based on ternary eutectic solvent and preparation method thereof

CN116535987BActive Publication Date: 2026-10-16SHANDONG UNIV OF TECH +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310333742.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2026-10-16
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

该专利的优点在于,既能实现抗菌消炎、加快伤口愈合,又安全无刺激;但缺点在于,该材料较难实现降解

Benefits of technology

[0037] (1) The ternary eutectic solvent prepared in this invention is formed by blending tetradecyl dimethyl benzyl ammonium chloride, chitosan, and oligolactic acid. Tetradecyl dimethyl benzyl ammonium chloride acts as an antibacterial agent and hydrogen bond acceptor, chitosan acts as an antibacterial agent and hydrogen bond donor, and oligolactic acid acts as a hydrogen bond donor. By introducing double hydrogen bonds through the formation of the ternary eutectic solvent, a more complex hydrogen bond network structure is formed than that of binary eutectic solvents, providing a broader operational window for regulating the viscoelasticity and antibacterial activity of the adhesive system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116535987B_ABST
    Figure CN116535987B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of high polymer materials, and particularly relates to a degradable adhesive tape based on a ternary eutectic solvent and a preparation method thereof. The degradable adhesive tape based on the ternary eutectic solvent comprises a backing material, an adhesive layer and a release agent layer, the adhesive layer, the backing material and the release agent layer are sequentially connected from top to bottom, and the adhesive in the adhesive layer is prepared from 10-20 parts of tetradecyl dimethyl benzyl ammonium chloride, 10-15 parts of chitosan, 15-30 parts of oligomeric lactic acid, 40-50 parts of polycarbonate elastomer, 0.2-0.6 parts of an antioxidant and 5-10 parts of a softening agent. The ternary eutectic solvent is prepared from the oligomeric lactic acid, the tetradecyl dimethyl benzyl ammonium chloride and the chitosan, which not only plays a role in combined antibiosis, but also improves the durability of antibiosis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a biodegradable tape based on a ternary eutectic solvent and its preparation method. Background Technology

[0002] Adhesive tape is a bonding material composed of a substrate and an adhesive. It connects two or more unconnected objects together. The surface of the tape is coated with adhesive. In the 19th century, rubber was the main component of adhesives, while modern tapes widely use various adhesive polymers, utilizing the bonds formed between the molecules of the tape and the molecules of the objects to be bonded. The substrate is generally made of plastic materials, such as polypropylene film (BOPP) and polyester film (PET). With increasing human demand for adhesive tape, the recycling and disposal of waste tape has become a major problem. Carelessly discarded adhesive tape products cause "white pollution," as they are difficult to degrade under natural conditions, typically taking 200 to 400 years to degrade. This not only seriously damages the environment, causing soil degradation, affecting crop growth, and harming water quality, but also causes illness and even death in livestock if ingested. Furthermore, plastic products entering waste treatment plants are highly susceptible to producing greenhouse gases during high-temperature processing, contributing to ozone layer depletion. Therefore, in order to meet the requirements of green development, circular development and low-carbon development, and to provide favorable conditions for the recycling and disposal of tape waste, it is an inevitable trend to develop a new type of environmentally friendly tape.

[0003] Since the beginning of the 21st century, the rise of bio-based materials has provided numerous opportunities for the sustainable development of humankind. Polylactic acid (PLA) officially entered the Chinese market in 2004. Widely sourced, environmentally friendly, and non-polluting, PLA is a sustainable ecological fiber with promising development prospects. Modified PLA materials, in particular, meet diverse development needs due to their inherent advantages. However, the production of PLA generates 4%-7% oligolactic acid byproducts. These byproducts reduce PLA yield and corporate profits, while increasing waste disposal costs. Research has found that while low molecular weight PLA lacks elasticity, it possesses a certain degree of viscosity. Aliphatic polycarbonates such as polytrimethylene carbonate and polymethyl ethylene carbonate can serve as bioelastomers, exhibiting good flexibility and elasticity, as well as excellent biocompatibility and biodegradability. They do not produce strong acidic substances after degradation and can be widely used in the biomedical field. This provides advantageous conditions for the application of aliphatic polycarbonates and PLA in the production of environmentally friendly biodegradable tapes.

[0004] Quaternary ammonium salts containing amino cations typically possess antibacterial properties. These antibacterial agents can adsorb onto the bacterial surface using their own cations, disrupting the cell wall and cell membrane, causing cytoplasmic leakage and thus achieving sterilization. They exhibit excellent characteristics such as low toxicity, high bactericidal efficiency, rapid action, and a broad antibacterial spectrum. Chitosan is a natural antibacterial agent widely found in the shells of shrimp, crabs, insects, and algae cell walls, and its bactericidal mechanism is similar to that of quaternary ammonium salt antibacterial agents. However, directly adding either of these to adhesive formulations can lead to phase separation due to solubility issues and premature release, which is detrimental to long-lasting antibacterial effects and extending the tape's lifespan. Therefore, a reasonable formulation adjustment is needed to fully utilize the biodegradability of polylactic acid (PLA) while considering the chemical structural characteristics of quaternary ammonium salt antibacterial agents, chitosan, and PLA. A proper ratio of these components is crucial to addressing the technical challenges related to the viscoelasticity of PLA and the antibacterial activity of the tape.

[0005] Chinese patent CN111996794A discloses a method for preparing antibacterial polylactic acid (PLA) nonwoven materials. The method involves pretreating the PLA nonwoven material with atmospheric pressure argon DBD plasma, then grafting the PLA onto the surface using chitosan, a natural polymer, to generate nano-silver in situ on the PLA nonwoven material surface, thereby achieving antibacterial properties. The advantages of this patent are that it uses natural chitosan as an antibacterial agent, making it environmentally friendly, and the nano-silver exhibits excellent and long-lasting antibacterial properties. However, the disadvantages are that the production process is complex, requires specific production conditions, and the nano-silver particles are difficult to distribute evenly on the PLA surface.

[0006] Chinese patent CN115558152A discloses a double-drying biodegradable nanocellulose composite antibacterial aerogel, its preparation method, and its application. It uses Ti3C2TxMXene intercalated montmorillonite as a template and chitosan quaternary ammonium salt as a reducing agent to prepare an MXene-intercalated montmorillonite immobilized nano-silver composite antibacterial agent. Then, using nanocellulose as a matrix, it mixes with the immobilized nano-silver composite antibacterial agent and prepares the nanocellulose / MXene-montmorillonite-nano-silver composite antibacterial aerogel through a "double-drying" technique. The advantages of this patent are that the MXene-montmorillonite-nano-silver aerogel has a long-lasting antibacterial effect, excellent antibacterial performance, and is biodegradable. However, the disadvantage is that the silver ammonia solution used in this patent can produce silver azide (AgN3) after prolonged storage, which may cause an explosion. Direct discharge would cause environmental pollution and waste silver resources.

[0007] Chinese patent CN115444992A discloses an absorbable anti-adhesion material and its preparation method. The absorbable anti-adhesion material includes an antibacterial and anti-inflammatory layer A (which may use chitosan quaternary ammonium salt as an antibacterial agent) and an anti-adhesion layer B. The anti-adhesion material has a large specific surface area and forms a three-dimensional network structure upon contact with body fluids, which is conducive to cell proliferation and climbing, accelerating wound healing and effectively preventing tissue adhesion after wound repair. The advantage of this patent is that it achieves antibacterial and anti-inflammatory effects, accelerates wound healing, and is safe and non-irritating; however, the disadvantage is that the material is difficult to degrade. Summary of the Invention

[0008] The purpose of this invention is to provide a biodegradable tape based on a ternary eutectic solvent. This ternary eutectic solvent, prepared from oligolactic acid, tetradecyl dimethyl benzyl ammonium chloride, and chitosan, not only provides a combined antibacterial effect but also improves the durability of the antibacterial properties. The tape's biodegradability stems from its main component, polylactic acid, while chitosan, as a biomass material, also exhibits good biodegradability, thus meeting the needs of future sustainable development. This invention also provides a method for preparing the biodegradable tape based on the ternary eutectic solvent.

[0009] The biodegradable tape based on a ternary eutectic solvent of the present invention includes a backing material, an adhesive layer, and a release agent layer, which are connected sequentially from top to bottom. The adhesive in the adhesive layer is made of 10-20 parts of tetradecyl dimethyl benzyl ammonium chloride, 10-15 parts of chitosan, 15-30 parts of oligolactic acid, 40-50 parts of polycarbonate elastomer, 0.2-0.6 parts of antioxidant, and 5-10 parts of softener.

[0010] The molecular weight of the oligolactic acid is 600-2000.

[0011] The polycarbonate elastomer is one or more of polytrimethylene carbonate (PTMC), trimethylene carbonate-lactide copolymer, or polymethyl ethylene carbonate (PPC).

[0012] The antioxidant mentioned is antioxidant 2246.

[0013] The softener is naphthenic oil KN 4006.

[0014] The method for preparing the adhesive includes the following steps:

[0015] (1) Preheat the softener to obtain the preheated softener;

[0016] (2) Tetradecyl dimethyl benzyl ammonium chloride, chitosan and oligolactic acid are mixed to prepare a ternary eutectic solvent;

[0017] (3) Add the ternary eutectic solvent, polycarbonate elastomer and antioxidant to the preheated softener and blend to obtain the adhesive.

[0018] The preheating temperature mentioned in step (1) is 80-100℃ and the preheating time is 1.0-2.5h.

[0019] The mixing temperature in step (2) is 80-100℃ and the mixing time is 0.5-1.5h.

[0020] The blending temperature in step (3) is 80-100℃ and the blending time is 0.5-2.5h.

[0021] The backing material is a polylactic acid film.

[0022] The polylactic acid film has a molecular weight of 60,000-300,000 and a film thickness of 0.01-0.3 mm.

[0023] The release agent in the release agent layer is methyl vinyl silicone rubber.

[0024] The method for preparing the biodegradable tape based on a ternary eutectic solvent described in this invention is to first coat a release agent onto one side of a backing material, then heat and soften the adhesive before coating it onto the other side of the backing material, cool it to room temperature, and cure it to obtain the biodegradable tape based on a ternary eutectic solvent.

[0025] The amount of the release agent applied to the backing material is 0.25-3.0 g / m². 2 .

[0026] The amount of adhesive applied to the backing material is 0.5-3.0 g / m². 2 .

[0027] The heating temperature is 80-100℃.

[0028] The specific preparation steps for polytrimethylene carbonate (PTMC) are as follows:

[0029] (1) Place a stirring magnet into a single-necked flask, add 14.5 ml of 1,3-propanediol, 37.9 ml of ethyl chloroformate and 240 ml of tetrahydrofuran into the flask, and cool with an ice-salt bath.

[0030] (2) Under the conditions of ice-salt bath and magnetic stirring, 58 ml of triethylamine was slowly added dropwise using a constant pressure dropping funnel. An external drying tower was connected. After the addition was completed, the reaction was continued in an ice-water bath for 30 min. Then the ice-water bath was removed and the reaction was allowed to proceed at room temperature for two hours.

[0031] (3) Filter the reaction mixture to remove the white powdery solid of triethylamine hydrochloride. Concentrate the filtrate using a rotary evaporator. Then, pour the concentrated filtrate into an excess of anhydrous diethyl ether for redeposition, precipitating a white solid. Filter the filtrate again and collect the solid product.

[0032] (4) The solid product was recrystallized 3-5 times with an anhydrous tetrahydrofuran-diethyl ether mixed solution, and the product was dried under vacuum to constant weight to finally obtain white crystals of trimethylene carbonate (TMC).

[0033] (5) Take 2.04g of trimethylene carbonate and 10μl of 0.1mol / l stannous octoate-toluene solution and add them to the polymerization tube. Evacuate the tube and replace it with nitrogen. Use an alcohol torch to seal the tube under reduced pressure.

[0034] (6) The polymerization tube was placed in an oil pan and heated to 130°C for 72 hours. The final product was dissolved in dichloromethane, reprecipitated with methanol, and then filtered to obtain polytrimethylene carbonate (PTMC) elastomer.

[0035] In this invention, tetradecyl dimethyl benzyl ammonium chloride, chitosan, and oligolactic acid form a complex hydrogen bond network through a ternary eutectic solvent. Both tetradecyl dimethyl benzyl ammonium chloride and chitosan act as antibacterial agents; compared to single-component antibacterial agents, the combined antibacterial effect of the two components enhances the antibacterial activity of the prepared tape. Furthermore, compared to binary eutectic solvents with only single hydrogen bonds, the ternary eutectic solvent introduces double hydrogen bonds, which increases intermolecular forces and enhances the cross-linking degree of the hydrogen bond network, thereby strengthening the constraint on the release of antibacterial components and improving the long-term antibacterial effect. The prepared biodegradable tape is partially derived from biomass materials, aligning with current development trends and providing an effective solution to the "white pollution" problem, while also meeting the specific needs of clinical medicine and packaging fields.

[0036] The beneficial effects of this invention are as follows:

[0037] (1) The ternary eutectic solvent prepared in this invention is formed by blending tetradecyl dimethyl benzyl ammonium chloride, chitosan, and oligolactic acid. Tetradecyl dimethyl benzyl ammonium chloride acts as an antibacterial agent and hydrogen bond acceptor, chitosan acts as an antibacterial agent and hydrogen bond donor, and oligolactic acid acts as a hydrogen bond donor. By introducing double hydrogen bonds through the formation of the ternary eutectic solvent, a more complex hydrogen bond network structure is formed than that of binary eutectic solvents, providing a broader operational window for regulating the viscoelasticity and antibacterial activity of the adhesive system.

[0038] (2) The tetradecyl dimethyl benzyl ammonium chloride and chitosan used in this invention both have antibacterial activity. They achieve a synergistic effect by forming a eutectic solvent. On the basis of enhancing antibacterial activity, the complex hydrogen bond network restricts the early release, which is beneficial to improving the long-term antibacterial effect of the adhesive.

[0039] (3) The present invention uses low molecular weight oligolactic acid, which contains a large amount of -COOH. By forming a ternary eutectic solvent with tetradecyl dimethyl benzyl ammonium chloride and chitosan, it not only makes full use of the unpolymerized -COOH to form a complex hydrogen bond network structure, but also allows for the regulation of the rheological properties of the adhesive layer by forming a eutectic solvent.

[0040] (4) The polycarbonate elastomer selected in this invention has good compatibility with ternary eutectic solvent and softener, which not only helps to improve the elasticity of the adhesive, but also has good degradability and does not affect the overall degradability of the prepared tape.

[0041] (5) The tapes in this invention are all made of biodegradable materials. The raw materials are cheap and readily available, non-toxic and non-polluting, and the preparation process is simple. They do not generate environmental pollution waste, and take into account both economy and environmental protection. They have good application prospects. Attached Figure Description

[0042] Figure 1 It is the hydrogen NMR spectrum of oligolactic acid.

[0043] Figure 2 This is the 1H NMR spectrum of tetradecyl dimethyl benzyl ammonium chloride.

[0044] Figure 3 This is the hydrogen NMR spectrum of chitosan.

[0045] Figure 4 It is a ternary eutectic solvent NMR hydrogen spectrum.

[0046] Figure 5 This is a comparison of the 1H NMR spectra of a ternary eutectic solvent, chitosan, oligolactic acid, and tetradecyl dimethyl benzyl ammonium chloride. Detailed Implementation

[0047] The present invention will be further described below with reference to embodiments.

[0048] Example 1

[0049] The composition of the adhesive is shown in Table 1.

[0050] Table 1. Composition of the adhesive in Example 1

[0051]

[0052] The preparation method of the adhesive includes the following steps:

[0053] (1) The naphthenic oil KN 4006 was heated and stirred at 90℃ for 1.0h at a stirring rate of 150r / min to obtain the preheated naphthenic oil KN 4006.

[0054] (2) Under a nitrogen atmosphere, tetradecyl dimethyl benzyl ammonium chloride, chitosan and oligolactic acid (molecular weight 1000) were heated and mixed at 100°C for 0.5 h to prepare a ternary eutectic solvent.

[0055] (3) Under a nitrogen atmosphere, the ternary eutectic solvent obtained in step (2), PTMC, and antioxidant 2246 are added to the preheated naphthenic oil KN 4006 obtained in step (1), heated and mixed at 100°C for 1 hour with a stirring rate of 150 r / min, discharged, cooled, and the adhesive is obtained.

[0056] The preparation method of biodegradable adhesive tape based on ternary eutectic solvent includes the following steps:

[0057] (1) Apply methyl vinyl silicone rubber release agent to one side of the polylactic acid film backing using a coating machine, with a coating amount of 0.25 g / m. 2 The polylactic acid (PLA) film has a molecular weight of 60,000 and a film thickness of 0.02 mm.

[0058] (2) Heat the adhesive to 90°C to soften it, and then apply it to the other side of the backing material at a coating amount of 0.5 g / m. 2 After being cooled and cured at room temperature, a biodegradable tape based on a ternary eutectic solvent is obtained.

[0059] Circular initial tack test: Using GB / T 31125-2014, the circular initial tack of the tape was measured to be 7.75 N.

[0060] 180° peel force: Using GB / T 2792-2014, the 180° peel force of the tape was measured to be 0.580 kgf.

[0061] Antibacterial performance test: The tape was cut into round pieces (Ф10.0cm), the adhesive layer was rinsed and dried, and the antibacterial performance of the adhesive layer of the round pieces against three types of bacteria was tested using the film adhesion method. The bacteria used were Staphylococcus aureus (S. aureus ATCC29213), Escherichia coli (E. coli ATCC25922), and Candida albicans (C. albicans ATCC10231). First, the freeze-dried bacteria of each strain were mixed with Sabouraud broth, and 2 ml of the bacterial suspension was incubated at 37℃ for 24 h. The freeze-dried bacteria were activated by subculturing twice using an inoculation loop. Then, 1×10⁻⁶ bacteria were prepared using the McFarland turbidimetric method. 5CFU / mL bacterial suspension was diluted, and 0.2 mL of the 0.2 mL suspension was dropped onto the surface of the tape disc sample to be tested. A sterilized polyethylene film was then placed on top, and the sample was incubated anaerobically at 37°C (80% N2, 10% CO2, 10% H2) for 48 h. Finally, the tape disc sample and polyethylene film were thoroughly washed with 20 mL of 0.9% NaCl aqueous solution. After shaking well, 500 μL of the eluent was inoculated into TSA medium, and colony counts were performed after 24 h of incubation. Each group of tape disc samples was tested five times, and the average colony count was used to calculate the antibacterial rate: Antibacterial rate = (Number of recovered bacteria in blank control sample - Number of recovered bacteria in experimental group sample) / Number of recovered bacteria in blank control sample × 100%. For the freshly prepared tape, the antibacterial rate was 99.91% for *S. aureus*, 99.95% for *E. coli*, and 99.89% for *C. albicans*. Accelerated aging test of tape samples: The tape samples were stored in a constant temperature chamber at 55℃ for 21 days. After being taken out, the above antibacterial performance test was repeated. The antibacterial rate of S. aureus of the tape after 21 days of aging was 97.32%, the antibacterial rate of E. coli was 97.01%, and the antibacterial rate of C. albicans was 96.97%.

[0062] Aging and Degradation Test: The adhesive tape was made into 1cm x 1cm squares with a thickness of 0.1mm and placed in small glass vials containing pH 8.0 phosphate buffer solution (Tris-HCl buffer system). The concentration of proteinase K (Genview) in the vials was 0.2 mg / ml. The temperature was set at 45℃, and the test was conducted with shaking at 140 rpm. Samples were removed at specified time intervals, washed with distilled water, and dried under vacuum until constant weight. The mass of the sample was then measured. The weight loss rate (W) of the sample was recorded. L Calculated using the following formula: Where m o It is the weight of the sample before degradation, m i This is the weight of the sample after degradation. M was measured 7 days after degradation. L The degradation rate was 76%, and M after 30 days was [missing information]. L It is 92%.

[0063] Example 2

[0064] The composition of the adhesive is shown in Table 2.

[0065] Table 2. Composition of the adhesive in Example 2

[0066]

[0067] The preparation method of the adhesive includes the following steps:

[0068] (1) The naphthenic oil KN 4006 was heated and stirred at 95℃ for 1.5h at a stirring rate of 150r / min to obtain the preheated naphthenic oil KN 4006.

[0069] (2) A ternary eutectic solvent was prepared by heating tetradecyl dimethyl benzyl ammonium chloride, chitosan and oligolactic acid (molecular weight 1000) at 90°C for 1 h under a nitrogen atmosphere.

[0070] (3) Under a nitrogen atmosphere, the ternary eutectic solvent obtained in step (2), the trimethylene carbonate-lactide copolymer, and antioxidant 2246 were added to the preheated naphthenic oil KN 4006 obtained in step (1), heated and mixed at 80°C for 2.5 h, with a stirring rate of 150 r / min, discharged, cooled, and the adhesive was obtained.

[0071] The preparation method of biodegradable adhesive tape based on ternary eutectic solvent includes the following steps:

[0072] (1) Apply methyl vinyl silicone rubber release agent to one side of the polylactic acid film backing using a coating machine, with a coating amount of 1.0 g / m. 2 The polylactic acid (PLA) film has a molecular weight of 150,000 and a film thickness of 0.05 mm.

[0073] (2) Heat the adhesive to 90°C to soften it, and then apply it to the other side of the backing material at a coating amount of 1.5 g / m. 2 After being cooled and cured at room temperature, a biodegradable tape based on a ternary eutectic solvent is obtained.

[0074] Annular initial tack test: The test method is the same as in Example 1. The measured annular initial tack was 7.63 N;

[0075] 180° peel force: The test method is the same as in Example 1. The measured 180° peel force is 0.569 kgf;

[0076] Antibacterial performance test: The test method is the same as in Example 1. For the freshly prepared tape, the antibacterial rate was measured to be 99.87% for *S. aureus*, 99.90% for *E. coli*, and 99.93% for *C. albicans*. After 21 days of aging, the antibacterial rate for the tape was measured to be 97.42% for *S. aureus*, 96.98% for *E. coli*, and 96.80% for *C. albicans*.

[0077] Aging degradation test: The test method is the same as in Example 1. M was measured after 7 days of degradation. L The degradation rate was 72%, and M was 72% after 30 days. L It is 88%.

[0078] Example 3

[0079] The composition of the adhesive is shown in Table 3.

[0080] Table 3. Composition of the adhesive in Example 3

[0081]

[0082] The preparation method of the adhesive includes the following steps:

[0083] (1) The naphthenic oil KN 4006 was heated and stirred at 100℃ for 2.5h at a stirring rate of 150r / min to obtain the preheated naphthenic oil KN 4006.

[0084] (2) A ternary eutectic solvent was prepared by heating tetradecyl dimethyl benzyl ammonium chloride, chitosan and oligolactic acid (molecular weight 2000) at 80°C for 1.5 h under a nitrogen atmosphere.

[0085] (3) Under a nitrogen atmosphere, the ternary eutectic solvent obtained in step (2), polycarbonate elastomer (PTMC to PPC mass ratio of 3:1), and antioxidant 2246 are added to the preheated naphthenic oil KN 4006 obtained in step (1), heated and mixed at 90°C for 2 hours, with a stirring rate of 150 r / min, discharged, cooled, and the adhesive is obtained.

[0086] The preparation method of biodegradable adhesive tape based on ternary eutectic solvent includes the following steps:

[0087] (1) A methyl vinyl silicone rubber release agent is applied to one side of the polylactic acid film backing using a coating machine, with a coating amount of 3.0 g / m. 2 The polylactic acid (PLA) film has a molecular weight of 300,000 and a film thickness of 0.3 mm.

[0088] (2) Heat the adhesive to 100°C to soften it, then apply it to the other side of the backing material at a coating amount of 3.0 g / m². 2 After being cooled and cured at room temperature, a biodegradable tape based on a ternary eutectic solvent is obtained.

[0089] Annular initial tack test: The test method is the same as in Example 1. The measured annular initial tack was 7.71 N;

[0090] 180° peel force: The test method is the same as in Example 1. The measured 180° peel force is 0.589 kgf;

[0091] Antibacterial performance test: The test method is the same as in Example 1. For the freshly prepared tape, the antibacterial rate was measured to be 99.49% for *S. aureus*, 99.53% for *E. coli*, and 99.50% for *C. albicans*. After 21 days of aging, the antibacterial rate for the tape was measured to be 98.13% for *S. aureus*, 97.09% for *E. coli*, and 96.73% for *C. albicans*.

[0092] Aging degradation test: The test method is the same as in Example 1. M was measured after 7 days of degradation. L The degradation rate was 69%, and M after 30 days was... L It is 86%.

[0093] Comparative Example 1

[0094] The adhesive composition does not include tetradecyl dimethyl benzyl ammonium chloride, and the other steps are the same as in Example 1.

[0095] Ring-shaped initial tack test: The test method is the same as in Example 1. The measured ring-shaped initial tack is 6.73 N.

[0096] 180° peel force: The test method is the same as in Example 1. The measured 180° peel force is 0.470 kgf.

[0097] Antibacterial performance test: The test method is the same as in Example 1. For the freshly prepared tape, the antibacterial rate was measured to be 83.72% for *S. aureus*, 82.09% for *E. coli*, and 82.53% for *C. albicans*. After 21 days of aging, the antibacterial rate for the tape was measured to be 60.62% for *S. aureus*, 59.57% for *E. coli*, and 58.80% for *C. albicans*.

[0098] Aging degradation test: The test method is the same as in Example 1. M was measured after 7 days of degradation. L The degradation rate was 82%, and M after 30 days was [missing information]. L It is 98%.

[0099] Results Analysis: Comparative Example 1 lacked tetradecyl dimethyl benzyl ammonium chloride, meaning it lacked hydrogen bond acceptors. Having only hydrogen bond donors prevented the formation of a eutectic solvent. Compared to Example 1, the antibacterial tape of Comparative Example 1 exhibited decreased initial tack and 180° peel strength, primarily due to the reduced compatibility of the chitosan component with the existing adhesive system and the increased susceptibility to phase separation, thus affecting adhesive performance. Compared to Example 1, the newly prepared tape in Comparative Example 1 showed a lower antibacterial rate, due to the absence of the tetradecyl dimethyl benzyl ammonium chloride antibacterial component, preventing the combined antibacterial effect. The tape's antibacterial rate significantly decreased after 21 days of aging, mainly due to phase separation in the adhesive system and chitosan precipitation after aging. Chitosan was partially removed during the rinsing step of the sample pretreatment for antibacterial performance testing, resulting in a lower measured antibacterial rate after aging. Compared to Example 1, the antibacterial tape of Comparative Example 1 exhibited a faster degradation rate, closely related to the instability and susceptibility to phase separation in the adhesive system.

[0100] Comparative Example 2

[0101] Chitosan was not added to the adhesive composition, and the other steps were the same as in Example 1.

[0102] Ring-shaped initial tack test: The test method is the same as in Example 1. The measured ring-shaped initial tack is 7.67 N.

[0103] 180° peel force: The test method is the same as in Example 1. The measured 180° peel force is 0.569 kgf.

[0104] Antibacterial performance test: The test method is the same as in Example 1. For the freshly prepared tape, the antibacterial rate was measured to be 91.54% for *S. aureus*, 90.19% for *E. coli*, and 91.74% for *C. albicans*. After 21 days of aging, the antibacterial rate for the tape was measured to be 86.53% for *S. aureus*, 85.70% for *E. coli*, and 85.98% for *C. albicans*.

[0105] Aging degradation test: The test method is the same as in Example 1. M was measured after 7 days of degradation. L 75% degradation, M after 30 days L It is 91%.

[0106] Results Analysis: Comparative Example 2 lacked chitosan in its components, and tetradecyl dimethyl benzyl ammonium chloride formed a binary eutectic solvent with oligolactic acid instead of a ternary eutectic solvent. Compared with Example 1, the antibacterial tape of Comparative Example 2 showed a slight decrease in ring initial tack and 180° peel force. This is because although the system lacked chitosan and could not form a ternary eutectic solvent, oligolactic acid and tetradecyl dimethyl benzyl ammonium chloride could form a binary eutectic solvent, which could adjust the viscoelasticity of the adhesive system to a certain extent, and had a relatively small impact on the adhesive strength. Compared with Example 1, the antibacterial rate of the newly prepared tape in Comparative Example 2 was reduced. This was because the chitosan antibacterial component was missing, and the antibacterial effect of tetradecyl dimethyl benzyl ammonium chloride alone was not as good as the combined antibacterial effect of tetradecyl dimethyl benzyl ammonium chloride and chitosan. The antibacterial rate of the tape after 21 days of aging was reduced compared with that before aging, and also reduced compared with the data of Example 1. This is because the hydrogen bonding force in the binary eutectic solvent is weaker than that in the ternary eutectic solvent, making it difficult to achieve the restraining effect of the ternary eutectic solvent on tetradecyl dimethyl benzyl chloride as in Example 1. As a result, tetradecyl dimethyl benzyl chloride precipitated during the aging process and was partially removed in the rinsing step of the sample pretreatment for antibacterial performance testing, resulting in a reduced measured antibacterial rate.

[0107] Comparative Example 3

[0108] Oligolactic acid is not added to the composition of the adhesive, and the other steps are the same as in Example 1.

[0109] Ring-shaped initial tack test: The test method is the same as in Example 1. The measured ring-shaped initial tack is 2.54 N.

[0110] 180° peel force: The test method is the same as in Example 1. The measured 180° peel force is 0.139 kgf.

[0111] Antibacterial performance test: The test method is the same as in Example 1. For the freshly prepared tape, the antibacterial rate was measured to be 99.62% for *S. aureus*, 99.70% for *E. coli*, and 99.13% for *C. albicans*. After 21 days of aging, the antibacterial rate for the tape was measured to be 96.91% for *S. aureus*, 96.05% for *E. coli*, and 95.12% for *C. albicans*.

[0112] Aging degradation test: The test method is the same as in Example 1. M was measured after 7 days of degradation. L 75% degradation, M after 30 days L It is 88%.

[0113] Results Analysis: Comparative Example 3 lacked oligolactic acid, resulting in tetradecyl dimethyl benzyl ammonium chloride forming a binary eutectic solvent with chitosan instead of a ternary eutectic solvent. Compared to Example 1, the antibacterial tape in Comparative Example 3 showed significantly reduced initial tack and 180° peel strength. This was due to the absence of oligolactic acid as a tackifier, leading to an imbalance in the viscoelastic ratio of the adhesive (high elasticity, low tack), thus reducing the adhesive performance. Compared to Example 1, the antibacterial rate of the newly prepared tape in Comparative Example 3 did not change significantly. This is because the tetradecyl dimethyl benzyl ammonium chloride and chitosan in the binary eutectic solvent also exerted a combined antibacterial effect, achieving good antibacterial performance. The antibacterial rate of the tape after 21 days of aging was slightly lower than that of the newly prepared tape and also slightly lower than that of Example 1. This indicates that the absence of oligolactic acid prevents the formation of a ternary eutectic solvent, and the long-lasting antibacterial effect of a ternary eutectic solvent cannot be achieved solely by relying on a binary eutectic solvent.

[0114] Comparative Example 4

[0115] The adhesive composition does not include polycarbonate elastomers, and the other steps are the same as in Example 1.

[0116] Ring-shaped initial tack test: The test method is the same as in Example 1. The measured ring-shaped initial tack is 3.41 N.

[0117] 180° peel force: The test method is the same as in Example 1. The measured 180° peel force is 0.128 kgf.

[0118] Antibacterial performance test: The test method is the same as in Example 1. For the freshly prepared tape, the antibacterial rate was measured to be 98.43% for *S. aureus*, 99.05% for *E. coli*, and 98.12% for *C. albicans*. After 21 days of aging, the antibacterial rate for the tape was measured to be 96.95% for *S. aureus*, 96.48% for *E. coli*, and 96.96% for *C. albicans*.

[0119] Aging degradation test: The test method is the same as in Example 1. M was measured after 7 days of degradation. L The degradation rate was 81%, and M was degraded after 30 days. L It is 94%.

[0120] Results analysis:

[0121] Compared to Example 1, the antibacterial tape in Comparative Example 4 showed significantly reduced initial tack and 180° peel strength. This was due to the lack of polycarbonate elastomer, which disrupted the viscoelastic balance in the adhesive layer, resulting in low elasticity and high tack, thus compromising the tape's adhesive properties. Compared to Example 1, the antibacterial rate of the tape in Comparative Example 4 did not change significantly, indicating that the polycarbonate elastomer had no significant impact on the antibacterial effect. The antibacterial rate also did not change significantly after 21 days of aging, indicating that the polycarbonate elastomer had no significant impact on the long-term antibacterial effect. Compared to Example 1, the degradation rate of Comparative Example 4 was accelerated. This was because the lack of polycarbonate elastomer increased the fluidity of the adhesive, thereby accelerating the degradation rate.

[0122] The performance test results of the tapes in Examples 1-3 are shown in Table 4, and the performance test results of the tapes in Comparative Examples 1-4 are shown in Table 5.

[0123] Table 4. Test results of tape performance in Examples 1-3

[0124]

[0125]

[0126] Table 5. Test results of tape performance in Comparative Examples 1-4

[0127]

[0128] Nuclear magnetic resonance (NMR) 1 Chemical structure analysis of oligolactic acid, tetradecyl dimethyl benzyl ammonium chloride, chitosan, and ternary eutectic solvent was performed by 1H NMR, with CDCl3 as the solvent used in all cases.

[0129] oligolactic acid 1 The H NMR spectrum is shown in [reference]. Figure 1 The structural formula of oligolactic acid is as follows:

[0130]

[0131] The carboxyl hydrogen at the c-position is 5.35 ppm, the tertiary hydrogen at the a-position is 4.39, 5.13, and 5.06 ppm, and the methyl hydrogen at the b-position is 1.67 and 1.57 ppm.

[0132] Tetradecyl dimethyl benzyl ammonium chloride 1 The H NMR spectrum is shown in [reference]. Figure 2 The structural formula of tetradecyl dimethyl benzyl ammonium chloride is as follows:

[0133]

[0134] The benzene ring hydrogens at the ae positions are 7.61 and 7.41 ppm, the secondary hydrogens at the f position are 4.94 ppm, the methyl hydrogens at the g and h positions are 3.25 ppm, the methyl hydrogen at the I position is 0.86 ppm, and the other 26 secondary hydrogens are 1.24 ppm.

[0135] Chitosan 1 The H NMR spectrum is shown in [reference]. Figure 3 The structural formula of chitosan is as follows:

[0136]

[0137] The amino hydrogen at positions a and b is 1.58 ppm, and the secondary hydrogen at positions c and d is 1.27 ppm, indicating that the chitosan is composed of approximately 13 small molecules as shown in the structural formula.

[0138] A ternary eutectic solvent (tetradecyl dimethyl benzyl ammonium chloride, chitosan, and oligolactic acid in a mass ratio of 1.5:1:1.5) 1 The H NMR spectrum is shown in [reference]. Figure 4 .

[0139] Comparison of tetradecyl dimethyl benzyl ammonium chloride, oligolactic acid, chitosan, and ternary eutectic solvents 1 H NMR spectrum, see Figure 5 The absorption peaks indicated by the arrows at points A and B are the amino hydrogen and secondary hydrogen on the chitosan polymer chain, respectively. By comparison, the absorption peaks were found to shift to the left by 0.06 ppm and 0.02 ppm, respectively. The absorption peaks indicated by the arrows at points C, F, and G are the secondary hydrogen and benzene ring hydrogen in tetradecyl dimethyl benzyl ammonium chloride, respectively. By comparison, the absorption peaks were found to shift to the right by 0.04 ppm, 0.02 ppm, and 0.03 ppm, respectively. The absorption peaks indicated by the arrows at points D and E are the tertiary hydrogen in oligolactic acid. By comparison, the absorption peaks were found to shift to the right by 0.01 ppm and 0.04 ppm, respectively. This indicates that hydrogen bonding has formed between tetradecyl dimethyl benzyl ammonium chloride, oligolactic acid, and chitosan, which proves the formation of a ternary eutectic solvent.

Claims

1. A biodegradable tape based on a ternary eutectic solvent, comprising a backing material, an adhesive layer, and a release agent layer, wherein the adhesive layer, backing material, and release agent layer are sequentially connected from top to bottom, characterized in that... The adhesive in the adhesive layer is made of 10-20 parts tetradecyl dimethyl benzyl ammonium chloride, 10-15 parts chitosan, 15-30 parts oligolactic acid, 40-50 parts polycarbonate elastomer, 0.2-0.6 parts antioxidant and 5-10 parts softener; The molecular weight of the oligolactic acid is 600-2000, and the polycarbonate elastomer is one or more of polytrimethylene carbonate, trimethylene carbonate-lactide copolymer, or polymethyl ethylene carbonate. The method for preparing the adhesive includes the following steps: (1) Preheat the softener to obtain a preheated softener; (2) Tetradecyl dimethyl benzyl ammonium chloride, chitosan and oligolactic acid are mixed to prepare a ternary eutectic solvent; (3) Add the ternary eutectic solvent, polycarbonate elastomer and antioxidant to the preheated softener and blend to obtain the adhesive.

2. The biodegradable tape based on a ternary eutectic solvent according to claim 1, characterized in that... The antioxidant is antioxidant 2246, and the softener is naphthenic oil KN 4006.

3. The biodegradable tape based on a ternary eutectic solvent according to claim 1, characterized in that... The preheating temperature mentioned in step (1) is 80-100℃ and the preheating time is 1.0-2.5h.

4. The biodegradable tape based on a ternary eutectic solvent according to claim 1, characterized in that... The mixing temperature mentioned in step (2) is 80-100℃ and the mixing time is 0.5-1.5h.

5. The biodegradable tape based on a ternary eutectic solvent according to claim 1, characterized in that... The blending temperature in step (3) is 80-100℃ and the blending time is 0.5-2.5h.

6. The biodegradable tape based on a ternary eutectic solvent according to claim 1, characterized in that... The backing material is a polylactic acid film with a molecular weight of 60,000-300,000 and a film thickness of 0.01-0.3 mm. The release agent in the release agent layer is methyl vinyl silicone rubber.

7. A method for preparing a biodegradable adhesive tape based on a ternary eutectic solvent as described in any one of claims 1-6, characterized in that... First, the release agent is applied to one side of the backing material. Then, the adhesive is heated and softened before being applied to the other side of the backing material. After cooling to room temperature and curing, a biodegradable tape based on a ternary eutectic solvent is obtained.

8. The method for preparing biodegradable tape based on a ternary eutectic solvent according to claim 7, characterized in that... The amount of the release agent applied to the backing material is 0.25-3.0 g / m². 2 The amount of adhesive applied to the backing material is 0.5-3.0 g / m². 2 The heating temperature is 80-100℃.

Citation Information

Patent Citations

  • Preparation method of antibacterial polylactic acid non-woven material

    CN111996794A

  • Absorbable anti-adhesion material and preparation method thereof

    CN115444992A

  • Dual-drying degradable nanocellulose composite antibacterial aerogel as well as preparation method and application thereof

    CN115558152A

  • Dental adhesive, and preparation method and application thereof

    CN111297698A

  • Preparation method of antibacterial non-woven fabric medical dressings

    CN112030559A